Back Cover: Excited State Charge‐Transfer Complexes Enable Fluorescence Color Changes in a Supramolecular Cyclophane Mechanophore (Angew. Chem. Int. Ed. 42/2022). Issue 42 (30th September 2022) - Thazhathethil, Shakkeeb; Muramatsu, Tatsuya; Tamaoki, Nobuyuki; Weder, Christoph; Sagara, Yoshimitsu
Abstract : Mechanochromic mechanophores visualize stress applied to polymers. In their Communication (e202209225), Christoph Weder, Yoshimitsu Sagara et al. demonstrate the first cyclophane mechanophore utilizing charge–transfer complex emission. Polyurethane elastomer films in which the mechanophore is covalently embedded exhibit instantly reversible emission color change between orange and blue upon deformation. The spatial separation of the luminophore and quencher leads to vivid mechanochromic luminescence.